2020
DOI: 10.1590/pboci.2020.027
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Toothache on Daily Activities of Children Aged 5 to 9 Years in Kerman, Iran

Abstract: Objective: To investigate the impacts of toothache on the daily activities of children aged 5 to 9 years. Material and Methods: A cross-sectional analytical study was conducted among 465 children (220 boys and 245 girls) aged between 5-9 years, using the Child Dental Pain Questionnaire (Child-DPQ), in the city of Kerman. They were categorized into two groups based on the clinical status: (1) untreated dental caries and (2) no dental caries or treated dental caries. For data analysis, the Chi-square, Mann-Whitn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 29 publications
(70 reference statements)
0
10
0
Order By: Relevance
“…The analysis included a broad variety of populations, and there was significant heterogeneity in pain measurement tools, which may account for the wide range in dental pain prevalence observed in this analysis. Where standardized questionnaires were used to assess pain, the Dental Discomfort Questionnaire and Child Dental Pain Questionnaire were commonly adapted for use 61,68,78,87,88,90–92 …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The analysis included a broad variety of populations, and there was significant heterogeneity in pain measurement tools, which may account for the wide range in dental pain prevalence observed in this analysis. Where standardized questionnaires were used to assess pain, the Dental Discomfort Questionnaire and Child Dental Pain Questionnaire were commonly adapted for use 61,68,78,87,88,90–92 …”
Section: Resultsmentioning
confidence: 99%
“…Multiple studies have reported a significant association between dental pain and caries, 58,59,61,68–71,74–78,88,92,93 while molar incisor hypomineralization, ulceration, bleeding gums, missing teeth, filled teeth, and erupting molars have also been associated with dental pain 68,73–75,88 . An unhealthy diet, including the consumption of sugary or soft drinks, fried foods, sweets, and alcohol, was also indicated as a risk factor for dental pain 60,66,81,90 . Socioeconomic factors, including low monthly income, lower parental education level, non‐nuclear family structure, living in crowded housing, and attending a public school, were also identified as risk factors 3,60,64,66–68,70,71,75–77,79,81,88,90,92 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations